Factors Affecting the Quality of Financial Reports in Baznas North Sumatra - Hastuti Olivia; Nurlaila Nurlaila (Budapest International Research and Critics University, 2022)
This study aims to determine the factors that affect the quality of financial reports in Baznas throughout North Sumatra. This is related to the large number of Regency/City Baznas in North Sumatra that provide financial reports only on revenues and expenses. This study uses a quantitative method using SmartPLS 3.0. The research sample is all BAZNAS in North Sumatra registered in the 2019 National Zakat Index, which amounts to 12 Regency/City Baznas. The sample of this study were 52 people. From the initial data processing, it is known that the loading factor in this study is not below 0.7. The results of the study using boostraping are known that Human Resource Competence has an effect on the quality of financial reports with t table greater than t count 2.106 > 1.76, Computer Technology has no effect on the quality of financial reports because t table is smaller than t arithmetic 0.501 < 1.67, the application of PSAK 109 has no effect on the quality of financial statements because t table is smaller than t count 0.679 < 1.67.